Introducing the Contextual Ambidexterity Scale for Public Organizations (CASPO): Scale development and initial evidence - Nunes, F. G.; Nascimento, G.; Martins, L. (Administratie si Management Public, 2021)
Contextual ambidexterity describes the organizational capacity of being simultaneously able to adapt and change in the face contextual requirements while keeping alignment and predictability. Contextual ambidexterity has been recognized as an appropriate explanation of organizational performance, and its influence has already permeated accounts of public organizations’ dynamics. We join this line of reasoning by suggesting that some specific characteristics of public organizations call for refinement of the contextual ambidexterity concept, and the correspondent evolution in measuring this organizational ability, thus introducing the Contextual Ambidexterity Scale for Public Organizations (CASPO). We suggest going beyond the original measure of alignment and adaptability created by Gibson and Birkinshaw (2004), to include psychological safety, reflexive spaces, and flexibility as sub-dimensions of adaptability and imprinting, rule-following and shared vision as sub-dimensions of alignment. On the basis of a sample of civil servants (n=200), we used exploratory factor analysis to identify a six-dimensional solution covering alignment and adaptability. Using another sample of civil servants (n=200), we used confirmatory factor analysis to test CASPO’s construct validity and regression analysis in testing the criterion validity. The results reveal that CASPO shows appropriate metric qualities and that it surpasses Gibson and Birkinshaw’s (2004) scale in predicting both their measure of generic organizational performance and a measure of performance specific for public organizations. This study contributes to the creation of sound measures of relevant concepts explaining the performance of public organizations.